INTERNATIONAL FINANCIAL REPORTING STANDARDS (IFRS) IN ACCOUNTING AND THEIR PRACTICAL APPLICATION IN THE ACCOUNTING OF BIOLOGICAL ASSETS (Global Economic Review: Journal of Economics, Policy, and Business Development, 2026)
This article analyzes international financial reporting standards (IFRS) and their role in modern financial reporting. The main principles of IFRS – fair presentation, accrual basis, consistency, understandability, and comparability – are discussed. Additionally, the key components of financial statements are explained: statement of financial position, statement of profit or loss, cash flow statement, and statement of changes in equity. The article emphasizes the importance of valuing biological assets and other assets according to international standards. The benefits of complying with IFRS for companies, including increased investor confidence, attracting foreign investments, and improving the quality of financial decision-making, are highlighted. The article provides a general understanding of accounting and financial management in accordance with international standards.